NILAI-NILAI DAN MAKNA SIMBOLIK TRADISI NGANGGUNG DI DESA PETALING PROPINSI KEPULAUAN BANGKA BELITUNG - Waluyo, Muhamad Edy (Sabda: Jurnal Kajian Kebudayaan, 2015)
The tradition of Nganggung in Petaling Bangka, Province of Bangka Belitung Islands is a tradition that‘s been rooted in its community. Although the origins of this tradition being searches up to now has not been scrapped, when and who to become pioneers of this tradition.This research reveal about values and symbolic meanings of the Nganggung tradition in the village of Petaling in which in the tradition have these values: a. Spiritual, b. Economical, c. Mutual cooperation and togetherness and d. Politically. And in the other side also has a symbolic meaning, we can see it at Nganggung attributes ―tudung saji‖ represent the preservation of the indigenous plants of pandanus forest, as well as means of preserving of lofty values of its ancestors; from its shape, which resembles a parabole represents the tradition of Nganggung as a shelter for all; red, as dominant color of ―tudung saji‖ symbolizes courage and high work ethic; cords symbolizes the fastener with a diversity of community and a sense of belonging; a round pan (talam) shape symbolizes the dynamic attitude and flexibility of its inhabitants